ENVIRONMENTAL AND HYDRAULIC MONITORING USING CATIONIC DYES TO INVESTIGATE THE BARRIERS EFFECT ON KAOLIN DEPOSITION - A. AL-Mafraji, Ekram; A. Al-Mussawy, Haider (Journal of Engineering and Sustainable Development, 2021)
Dyes are used in hydraulic fields such as hydraulic tracking to show the flow path, monitor flow lines within a ground dam, or track the spread of contaminated water within horizontal pipes and environmental fields as environmental indicators in titrations, such as titration of precipitate composition. Some environmental experiments dispense with the dye's use because it interferes with other compounds, such as interfering with the turbidity readings even if non-reactive dyes, but the present study transformed this problem into a positive phenomenon to benefits from the dye in both fields. The research methodology includes a laboratory analysis using different parameters such as discharge of suspension, the volume of dye, and the percentage of initial water depth at maximum water depth also theoretical analysis of the previous research methodology. The experimental results show that cationic dyes' absorption (methylene blue dye, MB and crystal violet, CV) is directly proportional to the percentage of kaolin deposition in the sedimentation tank areas. Finally, MB and CV dyes are used in both fields in one trial (such as tracking flow movement, monitoring the vortices formed using baffles, and inter between the amount of kaolin precipitated in each zone the sedimentation). However, MB is the best compare to CV.